A Case Report of Posterior Shoulder Dislocation with Greater Tuberosity Fracture - Mutchamee, MD, Supamongkol; Pongsamakthai, MD, Wanjak (Journal of Southeast Asian Orthopaedics, 2022)
Purpose: Posterior shoulder dislocation with fracture of greater tuberosity of the humerus is extremely rare. Therefore, the best prescribed treatment for it has not yet been established. Methods: A 45-year-old male, the victim of motorcycle accident, presented with shoulder injury and deformity. Post injury radiographs demonstrated a posterior shoulder dislocation and hollow glenoid with bony fragments. Computed tomographic findings revealed a posterior shoulder dislocation with fracture of greater tuberosity of the humerus. A closed reduction procedure was successfully performed under general anesthesia. Results: Anatomical reduction of shoulder joint and greater tuberosity fragment was achieved with good joint stability. Conclusion: Closed reduction under general anesthesia is an effective treatment for posterior dislocation with fracture of greater tuberosity.